2004
DOI: 10.1111/j.1525-1594.2004.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Four Years’ Experience With a Miniaturized Extracorporeal Circulation System and Its Influence on Clinical Outcome

Abstract: It has been suggested that the morbidity associated with cardiopulmonary bypass can be attributed in part to the blood-material and blood-air interactions in the extracorporeal circulation (ECC). A recently introduced minimized ECC-system (MECC System) should be able to reduce these negative effects associated with ECC. A retrospective analysis was performed comprising 485 patients who were operated on for elective coronary artery bypass grafting (CABG) using the MECC System with intermittent antegrade warm bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
123
2
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(143 citation statements)
references
References 24 publications
10
123
2
8
Order By: Relevance
“…In a big series of 1.053 patients operated on with the MECC system, Immer et al reported a reduced troponine level release, a reduced postoperative release of IL-6 and also a low incidence of postoperative atrial fibrillation and an early extubation time. Similar results were already reported by others (Wiesenack 2004). In some prospective randomized trials comparing MECC and OPCAB, some Authors did not find dramatic difference between the two techniques.…”
Section: Miniaturized Extracorporeal Circulation and Isolated Cabg Opsupporting
confidence: 79%
“…In a big series of 1.053 patients operated on with the MECC system, Immer et al reported a reduced troponine level release, a reduced postoperative release of IL-6 and also a low incidence of postoperative atrial fibrillation and an early extubation time. Similar results were already reported by others (Wiesenack 2004). In some prospective randomized trials comparing MECC and OPCAB, some Authors did not find dramatic difference between the two techniques.…”
Section: Miniaturized Extracorporeal Circulation and Isolated Cabg Opsupporting
confidence: 79%
“…[7][8][9][10] The advantages of MECC for coronary surgery compared with conventional OPCABG have been documented with regard to less inflammatory activation, better global organ protection, 11,12 and a reduced need for blood transfusions. 4,13 In a mixed cohort of coronary and valvular patients, MECC proved technically attainable, versatile, and reliable for full extracorporeal perfusion with satisfactory control of postoperative morbidity. 14 Randomized controlled experiences indicate that MECC is more biocompatible than standard CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to OPCABG, in initial clinical experience MECC has proved to be safe, feasible, and superior to standard CPB in terms of postoperative complications. 4 Although a number of studies compare valve and coronary surgery with the use of MECC versus standard CPB, 5 no data are available on the outcomes of coronary revascularization with OPCABG versus MECC. We performed a direct comparison of the biocompatibility, early results, and 1-year outcome of myocardial revascularization with the use of either OPCABG or MECC.…”
mentioning
confidence: 99%
“…Οι συγγραφείς ανέφεραν λιγότερη αιµοαρραίωση και µειωµένη φλεγµονώδη απάντηση µε αυτά τα ελαχιστοποιηµένα κυκλώµατα [638][639][640][641][642][643]. Ο Abdel-Rahman και συν.…”
Section: είναι λογική η χρήση λιγότερων υγρών πλήρωσης και ελαχιστοποunclassified
“…[643] ανέφεραν µειωµένη ενεργοποίηση της πήξης και της ινωδόλυσης µε µειωµένα κυκλώµατα παράκαµψης και τόνισαν µειωµένη µετάγγιση σχετιζόµενη µε αυτά τα κυκλώµατα. Μια αναδροµική σύγκριση 970 ασθενών που υπεβλήθησαν εκλεκτικά σε CABG [639] και δύο προοπτικές τυχαιοποιηµένες µελέτες από την ίδια οµάδα [640,641] 400 ασθενών που υπεβλήθησαν εκλεκτικά σε CABG και 100 ασθενείς που υπεβλήθησαν σε αντικατάσταση αορτικής βαλβίδας ανέφεραν 50% τουλάχιστον µείωση στη συχνότητα µετάγγισης συµπυκνωµένων ερυθρών σε σύγκριση µε τα συµβατικά κυκλώµατα. Από την άλλη µεριά, δύο µικρότερες τυχαιοποιηµένες ελεγχόµενες µελέτες 30 και 204 ασθενών που υπεβλήθησαν σε CABG δε βρήκαν µείωση στις ανάγκες για µετάγγιση µε τη χρήση των δύο εµπορικά διαθέσιµων ελαχιστοποιηµένων κυκλωµάτων [642,644].…”
unclassified